Abundant, distinct, and seasonally dynamic bee community in the canopy‐aerosphere interface above a temperate forest. Issue 2 (15th February 2023) - Cunningham‐Minnick, Michael J.; Milam, Joan; Kane, Brian; Roberts, H. Patrick; King, David I.
Abstract: Our understanding of how bees (Apoidea) use temperate forests is largely limited to sampling the understory and forest floor. Studies over the last decade have demonstrated that bee communities are vertically stratified within forests, yet the ecology of bee assemblages immediately above the canopy, the canopy‐aerosphere interface, remains unexplored. We sampled and compared bee communities above the canopy of a temperate forest to the understory (1 m), midstory (10 m), and canopy (20 m) on the campus of the University of Massachusetts, in Amherst, Massachusetts, United States from April to August, 2021. Overall, we found that assemblages above the canopy had more bees than in the understory, were distinct in composition from all other strata, and included the greatest proportion of unique species. Bee abundance and species richness were highest in the understory throughout the spring (April and May) and decreased as the season progressed, while bee abundance and species richness at higher strata increased into the summer months. We also found that bees with preferences to nest in moist and rotting wood were largely restricted to canopy and midstory strata. We conclude that bee assemblages occupying the space above the forest canopy are abundant and diverse, and their unique composition suggests that this canopy‐aerosphere interface plays an additional role in the bee community of temperate forests. Alternatively, our findings question how forest bee communities should be defined while highlighting the need for research on fundamental processes governing species stratification in and above the canopy. Abstract : Vertical stratification of bee communities in temperate forests extends into the aerosphere, but the assemblage above the canopy is distinct from those within the forest. Most bees occupy the understory when floral resources of the forest are abundant in spring, but the bee community shifts into and above the canopy as the summer progresses and floral resources of the forest senesce. Examination of species life‐history traits demonstrated that wood‐nesting species remained within forest strata, while soil‐nesting species that were either males or females associated with open habitat, comprised the canopy‐aerosphere interface.